(untitled) (Journal of Computational Mathematics, 1999)
An efficient iteration-by-subdomain method (known as the Schwarz alternating algorithm) for incompressible viscous/inviscid coupled model is presented. Appropriate spectral collocation approximations are proposed. The convergence analysis shows that the iterative algorithms converge with a rate independent of the polynomial degree used.